Examining the Effectiviness of Jago Bank’s,Allo Bank’s, and Digibanks in Implementing Digital Transformation - Ireniza Diva Kanisa; Imronudin (IECON: International Economics and Business Conference, 2023)
The expansion of digital technology has affected the banking industry by giving each bank the chance to innovate and boost consumer loyalty in transactions. Products for digital banking services have been used to satisfy client needs without requiring customers to visit an office. Banking with digital technologies can boost internalefficiency and bank growth. This study employs a descriptive analytical research design with a quantitative approach to explain the object under study, identify specific issues with Indonesian digital banking firms, and assess the soundness of the digital banks at Bank Jago, Allo Bank, and Digibank in implementing cutting-edge technology. The Riskprofile, Good Corporate Governance, Earnings, and Capital (RGEC) technique is used toassess the health of banks. The examination of this study's findings shows that, overall, Bank Jago, Allo Bank, and Digibank are in good health, despite the fact that a few evaluation indicators are in poor health. Utilizing NPL and LDR, the risk profile for the credit risk component is evaluated. The Bank Jago NPL index predicts highly good resultsfor 2020-2021 and a healthy 2022. The outcomes of a very healthy bank condition are displayed in Allo Bank's NPL 2022 and in Digibank's NPL. Allo Bank is in good health,Digibank is in good health, however the LDR at Bank Jago is unhealthy. Bank Jago and Digibank's good corporate governance is capable of upholding GCG norms. In the interim, Allobank must repair GCG. This suggest that a sound bank can advance technological innovation. To compete in the age of digital technology, Allo Bank’s and Digibank’s advancements in their banking operations.